The Role of Cartilage Stem/Progenitor Cells in Cartilage Repair in Osteoarthritis - Hu, Ning; Qiu, Jingwen; Xu, Bo; Zhang, Shunhao; Guo, Zijian; Xie, Jing; Yang, Wenbin (Current Stem Cell Research & Therapy, 2023)
Osteoarthritis (OA) is a degenerative joint disease characterized by the loss of cartilage, which seriously affects the quality of patient's life and may even cause permanent sequelae. The treatment of OA is diversified, mostly limited to relieving clinical symptoms. Less invasive treatments that can cure OA are still lacking. With the rise of tissue-cell engineering, stem cell therapy has gradually aroused great interest in treating OA. Cartilage stem/progenitor cells (CSPCs), a type of stem cell found on the surface of articular cartilage, have many similarities with mesenchymal stem cells (MSCs). These cells can be isolated and cultured from animals and humans and exist in articular cartilage over the body, such as the knee joint, patellofemoral joint, and temporomandibular joint. Due to their strong proliferative and chondrogenic differentiation abilities, CSPCs may contribute a lot to cartilage regeneration and repair in OA. We will provide an overview of the biological characteristics of CSPCs and their role in OA in combination with the research progress. Despite some existing limitations, CSPCs still offer an innovative idea for OA treatment with great advantages.
Keywords: osteoarthritis